Development of spermatogenic cells and sperm quality after administration of pegagan extract (Centella asiatica) - Solihati M; Purwantara B; Supriatna I; Winarto A (Jurnal Ilmu Ternak dan Veteriner, 2013)
The purpose of this study was to determine the development of spermatogenic cells and sperm quality after administration extracts of pegagan (Centella asiatica) in various doses and duration of administration. The research was carried out with complete randomized design (CRD), consist of 16 combinations of dose and duration of treatment. Parameters measured consist of population of spermatogenic cells (spermatogonia, primary spermatocytes, late spermatids) and sperm quality (concentration, motility, abnormality). The data were processed using analysis of variance (ANOVA), and differences between treatments followed by Duncan test. The results show that both the dose and duration have very significantly (p < 0.01) affect on decreasing of late spermatid population, sperm motility and concentration, but not for population of spermatogonia, primary spermatocytes and sperm abnormalities. The decrease of population and quality may due to antifertility effect of pegagan, eventhough still in the normal range. It is concluded that spermatogenic cells development and sperm quality reduce after administration of pegagan extract, although infertility is not yet found up to the dose of 450 mg/kg BW for 49 days duration of administration. Key Words: Spermatogenic, Sperm Quality, Pegagan Extract